Jasmonate Signaling: Methods and Protocols - Goossens, Alain; Pauwels, Laurens (Methods in molecular biology, 2013)
Phenotyping Jasmonate Regulation of Senescence -- Characterizing Jasmonate Regulation of Male Fertility in Arabidopsis -- Phenotyping Jasmonate Regulation of Root Growth -- Bioassays for Assessing Jasmonate-Dependent Defenses Triggered by Pathogens, Herbivorous Insects, or Beneficial Rhizobacteria -- Elicitation of Jasmonate-Mediated Defense Responses by Mechanical Wounding and Insect Herbivory -- Pseudomonas syringae Infection Assays in Arabidopsis -- Jasmonate Signaling in the Field, Part I: Elicited Changes in Jasmonate Pools of Transgenic Nicotiana attenuata Populations -- Jasmonate Signaling in the Field, Part II: Insect-Guided Characterization of Genetic Variations in Jasmonate-Dependent Defenses of Transgenic and Natural Nicotiana attenuata Populations -- Profiling of Jasmonic Acid-Related Metabolites and Hormones in Wounded Leaves -- A Non-Targeted Approach for Extended Liquid Chromatography-Mass Spectrometry Profiling of Free and Esterified Jasmonates After Wounding -- Cell-Specific Detection of Jasmonates by Means of an Immunocytological Approach -- Jasmonic Acid-Amino Acid Conjugation Enzyme Assays -- Pull-Down Analysis of Interactions Among Jasmonic Acid Core Signaling Proteins -- Yeast Two-Hybrid Analysis of Jasmonate Signaling Proteins -- Modified Bimolecular Fluorescence Complementation Assay to Study the Inhibition of Transcription Complex Formation by JAZ Proteins -- Agroinfiltration of Nicotiana benthamiana Leaves for Co-Localization of Regulatory Proteins Involved in Jasmonate Signaling -- Electrophoretic Mobility Shift Assay for the Analysis of Interactions of Jasmonic Acid-Responsive Transcription Factors with DNA -- Transient Expression Assays in Tobacco Protoplasts -- Functional Analysis of Jasmonic Acid-Responsive Secondary Metabolite Transporters -- Expression Analysis of Jasmonate-Responsive Lectins in Plants -- Profiling the Jasmonic Acid Responses by Nuclear Magnetic Resonance-Based Metabolomics -- Metabolite Profiling of Plant Tissues by Liquid Chromatography Fourier Transform Ion Cyclotron Resonance Mass Spectrometry -- cDNA-AFLP-Based Transcript Profiling for Genome-Wide Expression Analysis of Jasmonate-Treated Plants and Plant Cultures -- Analysis of RNA-Seq Data with TopHat and Cufflinks for Genome-Wide Expression Analysis of Jasmonate-Treated Plants and Plant Cultures -- Transcriptome Coexpression Analysis Using ATTED-II for Integrated Transcriptomics/Metabolomics Analysis -- A Guide to CORNET for the Construction of Coexpression and Protein-Protein Interaction Networks.